(untitled) (Journal of Economic Research & Business Administration, 2022)
One of the main tasks of the state is to ensure the uniform development of the country as a whole. This can be achieved by equalizing the socio-economic development of the regions. The purpose of the analysis of the economic development of the region is to identify the existing imbalances and unused economic potential of self-development of the region for further substantiation of options for the strategy of economic development of the region. The main purpose of the integrated assessment of the regions of Kazakhstan, the analysis of the economic development of the East Kazakhstan region is to substantiate the need and find ways to strengthen it to determine the level and potential for further sustainable economic development of each region of Kazakhstan. The use of a system of statistical indicators in economic analysis; methods of charting and trends. The integrated assessment of the economic potential of the regions of Kazakhstan and its competitiveness was based on the final data of state statistics and economic indicators, as they cover a wide range of different economic aspects in the context of regions. The analysis is aimed, on the one hand, at identifying opportunities for increasing complexity in the economic development of the region, on the other hand, at assessing the conditions for its successful functioning in a market economy, based on the rational use of labor, material, natural and financial resources. Key words: regional economy, economic development, statistical indicators, economic problems, gross regional product, industry.